Implementasi Metode Filtering Berbasis Konten pada Sistem Informasi Penjualan di Bengkel Prima Motor - Darma, Jenshen; Darmanto, Tony; Kartono, Kartono (Universitas Multi Data Palembang, 2025)
The advancement of information technology has encouraged businesses, including automotive workshops, to optimize their operations. Bengkel Prima Motor, a motorcycle repair shop in Kalimantan Barat, still manually records sales transactions, leading to inefficiencies in inventory management and reporting. This study aims to develop a web-based sales information system to improve transaction efficiency and customer service. The research methodology includes observation, interviews, and literature studies, with system development using PHP and MySQL. The results indicate that the implementation of this system enhances operational efficiency, optimizes sales reporting, and improves customer experience. The system also supports better decision-making for inventory management.